Gangguan Kepribadian Tokoh Utama dalam Cerpen Thabliyyah Minas- Samā’ Karya Yusuf Idris - Eva Farhah; Afifah Wardatul Jannah (Al-Fathin: Jurnal Bahasa dan Sastra Arab, 2021)
This article discusses the personality disorder of the main character in the short story Thabliyyah Minas-Sama' by Yusuf Idris. The purpose of this study is to mention and describe personality disorders in the stories Thabliyyah Minas-Sama’ and the factors that cause the main character to experience personality disorders, both of which are problems in this study. The method used in this article is descriptive analysis method. The results of the research that has been carried out are as follows. First, there are seven personality disorders in Thabliyyah Minas-Sama' story, namely, (1) paranoid personality disorder, (2) schizoid personality disorder, (3) schizotypic personality disorder, (4) histrionic personality disorder, (5) narcissistic personality. disorder, (6) borderline personality disorder, (7) antisocial personality disorder. Second, the factors that cause personality disorders experienced by the main character in the story Tabliyyah Mina-Sama' by Yusuf Idris, namely (1) a bad experience, psychoanalysis which is suspected as neglect or exposure to violence by adults, (2) damage to the affiliation system such as failing to make friends. with other people, (3) experiencing stressful life events, (4) factors of low family income and living environment, (5) genetic factors that cause problems in regulating mood swings. Keywords: short story Thabliyyah Mina-Sama’, Personality disorders, factors causing personality disorders.